2010
DOI: 10.1093/pasj/62.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Method of the Particle-in-Cell Simulation for the Y-Point in the Pulsar Magnetosphere

Abstract: Recent observations in X-ray and Gamma-ray suggest that the emission region of the pulsar magnetosphere can be multifold. In particular, the open-close boundary of the magnetic field, so-called the Y-point, can be the place where magnetic field energy converts into the plasma heat and/or flow energy. Here, we present a new Particlein-Cell code in axisymmetric geometry, which can be applied to the Y-point of the pulsar magnetosphere. The electromagnetic solver is used in the two-dimensional grid points with the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Yuki & Shibata (2012) described very similar studies. Umizaki & Shibata (2010) focused on a detailed study of the Y-point in the aligned rotator, i.e. the cusp point of the last field line just grazing the light cylinder.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Yuki & Shibata (2012) described very similar studies. Umizaki & Shibata (2010) focused on a detailed study of the Y-point in the aligned rotator, i.e. the cusp point of the last field line just grazing the light cylinder.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…The inner edge of the neutral sheet, which is the open-close boundary of the magnetic field structure, is called Y-point. Umizaki & Shibata (2010) studied the Y-point via an axisymmetric particle-in-cell simulation. They demonstrated that the magnetic reconnection occurred quasi-periodically and thereby plasma was heated and accelerated.…”
Section: Discussionmentioning
confidence: 99%
“…We assume homogeneous wave fields in the direction perpendicular to the dipole geomagnetic field. The calculation is performed using the Buneman‐Boris method (Buneman, ; Umizaki & Shibata, ), which is suitable to follow trajectories of gyrating particles. Figure shows two examples of such calculations, as performed when the electrons are within the spatial and temporal domain of the wave profile.…”
Section: Theoretical Calculationsmentioning
confidence: 99%